Current knowledge about Devonian tentaculitoids of Amazonas and Parnaíba basins, Brazil, deposited in Brazilian institutions - Comniskey, Jeanninny Carla; Ghilardi, Renato Pirani; Bosetti, Elvio Pinto (Boletim do Museu Paraense Emílio Goeldi - Ciências Naturais, 2015)
The Tentaculitoids are commonly found in the outcrops of the Devonian of the Paraná Basin (Ponta Grossa and São Domingos Formation), the Amazon Basin (Maecuru and Ererê Formation) and Parnaíba Basin (Cabeças Formation). We analyzed 39 samples of scientific collections from the middle Devonian of the Amazon and Parnaíba Basin, with main objective to conduct a systematic review to refine the knowledge on the stratigraphic and paleogeographic distribution of the group. The species found were: Tentaculites trombetensis, Tentaculites stubeli, Tentaculites eldredgianus, Tentaculites oseryi and Styliolina clavulus. The species T. eldredgianus, T. trombetensis and S. clavulus were found in outcrops of Eifelian to the Givetian. While T. oseryi only during Givetian and T. stubeli during Eifelian. The first occurrences of tentaculitoids in South America are related to the Silurian, which corroborates the hypothesis that during the Early Silurian, there was a large increase in the diversity and quantity of tentaculitoids in the world.
Keywords: Tentaculitoidea; Systematic; Devonian; Palaeobiogeography; Amazonas Basin; Parnaíba Basin